PENINGKATAN MUTU LEMBAGA PAUD MELALUI PENDAMPINGAN TERSTRUKTUR DALAM PERSIAPAN AKREDITASI DI KECAMATAN SIKUR, LOMBOK TIMUR - Mohzana Mohzana; Muh. Jaelani Al Pansori (LPPM Institut Pendidikan Nusantara Global, 2025)
This Community Service (PkM) activity aims to enhance the readiness of Early Childhood Education (PAUD) institutions to undergo the accreditation process through structured assistance. Based on the initial mapping of 76 PAUD institutions in Sikur District, East Lombok, it was found that most institutions lacked a comprehensive understanding of the accreditation instruments and had yet to complete the required institutional documents by the National Standards for PAUD. This activity involved eight partner institutions and was carried out through three main stages: training on accreditation standards, assistance in preparing institutional documents, and simulation of filling out the digital instrument (Sispena 3.1). The method employed was participatory and field-based, with a hands-on approach and intensive mentoring. The results of the activity showed a significant improvement in institutional managerial capacity, digital skills of administrators, and the establishment of collaborative networks among PAUD institutions at the sub-district level. This mentoring program not only resulted in accreditation documents that meet the standards but also encouraged quality-based institutional transformation and fostered a reflective culture in educational governance. The implications of this activity indicate that a contextual and collaborative approach is effective in bridging the quality gap of PAUD institutions in the region.